Glyceryl behenate-based solid lipid nanoparticles as a carrier of haloperidol for nose to brain delivery: formulation development, in-vitro, and in-vivo evaluation - Yasir, Mohd (2023)
This study was aimed to develop the haloperidol (HPL) loaded solid lipid nanoparticles (SLNs) for brain targeting through the intranasal route. SLNs were fabricated by the emulsification diffusion technique using glyceryl behenate as lipid and tween 80 as a surfactant. SLNs were evaluated for particle size, zeta potential, structure, entrapment efficiency, solid state characterization by differential scanning calorimetry (DSC), and in-vitro release. In-vivo biological evaluation was performed on albino Wistar rats for the determination of pharmacokinetic as well as brain targeting parameters. Particle size, PDI, zeta potential, and entrapment efficiency of optimized formulation (HPL-SLNs 6) were found to be 103±09 nm, 0.190±0.029, -23.5±1.07 mV, and 79.46±1.97% respectively. In-vitro drug release studies exhibited that 87.21± 3.63% of the entrapped drug was released from the SLNs within 24 h. DSC curves confirmed that during entrapment in SLNs, the drug was solubilized in the lipid matrix and converted into the amorphous form. Enhanced HPL targeting to the brain was observed from HPL-SLNs as compared to HPL-Sol when administered intranasally. The value of AUC 0-∞ in the brain for HPL-SLNs i.n. was found to be nearly 2.7 times higher than that of HPL-Sol i.v., whereas 3.66 times superior to HPL-Sol administered i.n. Stability studies revealed that the formulation remains unchanged when stored at 4±2 °C (refrigerator) and 25±2 °C /60 ±5% RH up to six months. Finally, it could be concluded that SLN is a suitable carrier for HPL with enhanced brain targeting through i.n administration, as compared to the HPL-Sol, administered i.n. and i.v.